PENERAPAN SANKSI PIDANA TERHADAP USAHA RUMAH MAKAN YANG TIDAK MEMILIKI IZIN BERDASARKAN PERATURAN DAERAH KOTA PEKANBARU NOMOR 10 TAHUN 2000 TENTANG USAHA RUMAH MAKAN (STUDI KASUS KOTA PEKANBARU) - Supriyatmo '; Dessy Artina; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The conception of a State of law adopted by the State of Indonesia implies a written regulation in which the administration is based on the constitutional rule of the 1945 Constitution of the State of the Republic of Indonesia. In Local Regulation No. 10/2000 it is clearly regulated on business licenses and the extension of restaurant permits. Based on the findings that have been obtained by the authors in this study are still many restaurants in the jurisdiction of Pekanbaru city who run his restaurant business without permission and / or permit that has expired. Regional Regulation Number 10 Year 2000 concerning Restaurant Business, business license and extension of restaurant business permit have contained criminal sanction against restaurant without legal permit contained in Article 19 that can be threatened Penitentiary for 6 months or maximum penalty of five Million rupiah. In the area of Pekanbaru City itself there are many restaurants that do not have a valid permit, but still run their restaurant business activities. Based on the above chronology, according to the authors it is important to raise the research with the title of research